AN ANALYSIS CODE MIXING ON THE VIDEO OF MR. NADIEM MAKARIM’S MEETING - Leroy Holman Siahaan; Ali Hussin (Dialectical Literature and Educational Journal, 2020)
Sociolinguistics is a study of the connection between language and society. People have a different language style when they interact with each one. By many variations that they have, it can be possible for them to mix their language in their utterance—mixing one language with the other languages, in the sociolinguistics field, is called by code-mixing. It has been common to use of code-mixing in society. It happens in the one of the public figures and famous that is Mr. Nadiem Makariem. Therefore, this research focuses on code mixing that emerges on video of Mr. Nadiem Makariem. The objective of this research is to find out the types and levels of code mixing that appear on the video. This research was descriptive qualitative method and the researchers act as the main instrument of this research. In collecting the data, this research utilized documentation method. This study employed content analysis focusing on analyzing the types of code mixing which defined by Hoffman and the levels of code mixing that argued by Suwito. Then, the result of types and levels of code mixing were counted by using Walizer’s formula. The result shows that there were 134 data in the types and levels of code mixing. In the types of code mixing, the highest type was intra-sentential of code mixing (88.8%) and the lowest type was involving a change of pronunciation (0%). While, in the levels of code mixing, word level (44.8%) becomes the dominant while word repetition (3%) and idiom (1.5%) were the lowest.